Health and Wellbeing. Active ageing for older adults in Ireland - Mc Garrigle, Christine; Kenny, Rose; Scarlett, Siobhan (The Irish Longitudinal Study on Ageing, Trinity College Dublin, 2017)
A pervading theme which resonates at each wave of data collection is the enormous contribution that adults aged 50 and over make to Irish society. This is evident both in the amount of care provided to others and in financial and other transfers. Contrary to perceptions, the overwhelming direction of transfers of time and financial assistance is to children and grandchildren. For example, adults aged 54 years and over who have children are more likely to provide financial assistance to their children (48%) than receive financial help from them (3%). Furthermore, half of adults aged 54 to 64 years and 65 to 74 years provide regular childcare for their grandchildren for an average of 36 hours per month. This facilitates labour market participation of parents and flexibility of schedules for unanticipated events. In the main, the consequences of such transfers are better health and well-being for the provider. For adults with living parents (14%), one quarter assisted their parent(s) with basic personal care while 43% provided help with other activities such as household chores, errands, shopping, and transportation. Half of older adults also provided financial help to their parent(s). Adults aged 50 years and older in Ireland are the backbone of our volunteer structure with more than half volunteering during the previous year and 17% doing so at least once per week. Again, volunteering is significantly associated with better mood and quality of life as is regular social participation i.e. sports and social clubs. Thus, we provide empirical support to the contention that, far from later years being a time characterised by decline and increased dependency, older adults continue to make valuable contributions to society, with many characterised by active citizenship and participation in the lives of their families and their communities.
Keywords: Ageing